Nursing Care for Pleural Effusion Patients Through Semifowler Position on Hemodynamic Status: A Case Report - Mas’ulyatul Hukmiyah; Muhamad Zulfatul A'la; Ika Adelia Susanti; Yudho Tri Handoko (KHD Production, 2025)
Pleural effusion is the accumulation of fluid in the pleural cavity or membrane that separates the inner chest wall from the lungs. Pleural effusion can affect hemodynamics because increased intrapleural pressure can push organs in the mediastinum. Providing a semi-fowler position is one of the nursing interventions that is expected to improve hemodynamic status in patients with pleural effusion. This study aims to determine the implementation of nursing care for patients with pleural effusion by applying the semi-fowler position to hemodynamic status in the Catleya Room, dr. Soebandi Hospital, Jember. The research method in this study uses a case study. The respondents and place in this study were Mr. T. with pleural effusion in the Catleya Room of RSD dr. Soebandi Jember. Semifowler position intervention was given for 3 days with a duration of 2 hours. The results of this study indicate that on the first day, there was a decrease in blood pressure, MAP, and respiratory rate. While the pulse rate and oxygen saturation increased. On the second and third day, of the application of the semifowler position, the results showed that there was a decrease in respiratory rate and an increase in pulse rate and oxygen saturation. While there were no hemodynamic changes in blood pressure and MAP. The conclusion of this study is that the implementation of the semi-Fowler position has an effect on hemodynamic status, especially on reducing respiratory rate and increasing pulse rate and oxygen saturation.